Demystifying Cell and Gene Therapy Orchestration in Supply Chain Technical Operations - Ajay Mutukula (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Cell and gene therapies (CGTs) represent a paradigm shift in modern medicine, utilizing living cells or genetic material as therapeutic agents rather than traditional pharmaceuticals. This revolutionary approach introduces extraordinary complexity to supply chain and technical operations management. The inherent variability of biological materials, coupled with the patient-specific nature of many CGTs, creates unprecedented challenges across the entire therapy journey. This article examines the unique characteristics of CGT supply chains, focusing on the critical differences between autologous (patient-derived) and allogeneic (universal) therapies and their distinct operational requirements. We explore the essential concepts of Chain of Custody and Chain of Identity that underpin safe and effective CGT delivery, analyzing how failures in these systems can lead to serious consequences. It provides a comprehensive overview of the end-to-end orchestration process, from patient identification through manufacturing to administration and follow-up monitoring. Additionally, It investigate the technological enablers that are transforming CGT supply chain management, including digital platforms, IoT monitoring systems, secure documentation technologies, and advanced analytics. The article also addresses the evolving regulatory landscape that governs these advanced therapies and examines emerging trends such as decentralized manufacturing, automation, standardized platforms, and artificial intelligence applications that promise to enhance the accessibility, reliability, and affordability of these potentially life-changing treatments.